MODELING TOWARDS FERTILITY PREFERENCE IN PAKISTAN - Jamal Abdul Nasir; Muhammad Imran; Syed Arif Ahmed Zaidi (Journal of University Medical & Dental College, 2019)
BACKGROUND: To access the socio demographic determinants that have potential inﬂuence on fertility preferences among Pakistani women of reproductive age 15-49. DATA: Pakistan Demographic and Health Survey (PDHS) of ever married women with sample size 13558 was used. SETTING: The National Institute of Population Studies coordinated this survey with the technical support from ICF International and Pakistan Bureau of Statistics and the USAID supported the ﬁnancially. METHODS: Bivariate and multinomial logistic regression analysis carried out. RESULTS: Higher proportion (42.6%) of women wants no more children. Bivariate analysis revealed that age, place of residence, education status, media access, wealth index, occupation, number of living children and ideal numbers of children are found to be signiﬁcant with respect to fertility preference. Multinomial model showed that younger women were almost ten times [OR=9.76] preferred more children compared to older ages. Respondents belong to Baluchistan and Sindh province [OR=1.59 OR=1.49] were likely to have more children respectively compared to their counter parts lived in GB. An illiterate woman 1.20 times more wants children compared to women with higher educational degree. Women belong to Sindh and Punjab 1.79 and 1.62 times more used modern contraception (sterilized) respectively. Women dweller of Baluchistan region were more likely to declare in fecund compared to their counter parts lived in Gilgit Baltistan. CONCLUSION: These statistical outcomes about fertility preference in Pakistan and exploration of signiﬁcant socio demographic factors of ever married women can be an emerging for population management and control.